STUDENTS' PERCEPTION OF ONLINE LEARNING IN LISTENING CLASS AT THE ENGLISH EDUCATION STUDY PROGRAM - Athyah, Andi Ummy; Korompot, Chairil Anwar; G, Hasriani (Universitas Negeri Makassar, 2023)
This research aims to find out the perceptions of English students towards online learning in listening classes. The method used in this research is a qualitative descriptive method. The participants in this research were students of the English Education Study Program class of 2023, Universitas Negeri Makassar. Eight students were selected as participants using a simple random sampling technique. The instrument used in this research was an interview analysis qualitatively and descriptively to determine the findings from the interview transcript. Overall, students had positive and negative perceptions of online learning in listening classes. The positive perceptions regarding online learning in the listening classes were expressed as follows 1) It is fun, 2) It improves listening skills 3) It is flexible 4) It involves the use of practical applications, e.g., Google Meet, and 5) It is applied using effective strategies. Meanwhile, the students’ negative perceptions of online learning in the listening classes were expressed as follows 1) it is technical constraints, and 2) it is non-technical constraints. Even though the students' perceptions varied, based on the data obtained, positive perceptions are more dominant than negative perceptions. Therefore, it can be concluded that students had a positive perception regarding online learning in listening classes.